Pengaruh Short Video Terhadap Peningkatan Maharah Qira’ah Siswa Kelas X MA Abu Darrin Bojonegoro - Mohammad Makinuddin; Asmaa Rosyida (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2025)
This research is motivated by the low Arabic text reading skills (maharah qira'ah) among 10th-grade students at Madrasah Aliyah Abu Darrin Sumbertelaseh Dander Bojonegoro, which is caused by the use of conventional learning methods that are less engaging. This study aims to analyze the effectiveness of using short videos in improving maharah qira'ah, particularly in reading Arabic texts correctly, including pronunciation and content comprehension. The study employed a quasi-experimental design with two groups: 30 students from class X-5 as the experimental group, who received short video-based learning, and 30 students from class X-6 as the control group, who used conventional methods. Data collection instruments included pre-test and post-test assessments of reading skills, which had undergone expert validation and reliability testing. Data were analyzed using descriptive statistical tests and t-tests with SPSS version 30. The results showed that learning with short videos had a significant impact on improving maharah qira'ah, as evidenced by a t-test value exceeding the significance threshold and a large effect size (Cohen’s d) of 0.804. The use of short videos significantly contributed to enhancing students' maharah qira'ah by enriching the learning process through engaging audiovisual elements, increasing motivation, and improving focus. With visual imagery, clear audio, and relevant contexts, short videos facilitated the understanding of Arabic texts and proved more effective than conventional methods. These findings confirm short videos as an innovative alternative learning medium that aligns with the needs of today's students, opening opportunities for the development of more creative and adaptive Arabic language learning methods in the future.